2015
DOI: 10.1007/s11011-015-9671-3
|View full text |Cite
|
Sign up to set email alerts
|

Maternal deprivation disrupts mitochondrial energy homeostasis in the brain of rats subjected to ketamine-induced schizophrenia

Abstract: Maternal deprivation (MD) appears to be one of the environmental factors involved in the pathophysiology of schizophrenia. A widely used animal model of the schizophrenia involves the administration of ketamine, a dissociative anesthetic, NMDA receptors noncompetitive antagonist, that induce symptoms such as schizophrenia. To clarify the molecular mechanism of schizophrenia induced by MD, we investigated alterations in energetic metabolism, oxidative stress and neurotrophic factor levels in the brain of rats f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 67 publications
1
9
0
Order By: Relevance
“…Findings of structure specific changes in the brain of MD rats in our investigations are in congruence with the findings of Zugno et al [57]. These authors have investigated the effects of MD conducted for 3 h per day during the first 10 days of life on the oxidative stress parameters in the cortex, hippocampus, and striatum of 60-day-old rats.…”
Section: Discussionsupporting
confidence: 92%
“…Findings of structure specific changes in the brain of MD rats in our investigations are in congruence with the findings of Zugno et al [57]. These authors have investigated the effects of MD conducted for 3 h per day during the first 10 days of life on the oxidative stress parameters in the cortex, hippocampus, and striatum of 60-day-old rats.…”
Section: Discussionsupporting
confidence: 92%
“… 13 In addition, obstetric events, such as hypoxia, and environmental insults later in life, such as social stress, are associated with oxidative stress and represent risk factors for SZ. 14 , 15 , 16 , 17 , 18 , 19 , 20 …”
Section: Sz Is Associated With Redox Imbalancementioning
confidence: 99%
“…Importantly, many pre-clinical models for MDD are induced by ELS, and consistently implicate mitochondrial mechanisms in the subsequent development of depressive behaviors (110). For example, in vivo models for MDD have shown that mitochondrial ETC complex activity is disrupted in brain tissue following maternal deprivation, social isolation, restraint stress, mild stress, and unpredictable stress (117)(118)(119)(120)(121)(122). Moreover, several transcriptomic studies have reported significant dysregulation of mitochondrial genes involved in lipid metabolism, oxidative phosphorylation (OXPHOS) and glucose homeostasis in preclinical models for chronic and acute stress (108,(123)(124)(125).…”
Section: Mitochondrial Allostatic Loadmentioning
confidence: 99%